Mapping, validation, and development of markers for the major adult plant stripe rust resistance locus QYr.hnk-7DL in Henan wheat - Xijun Du; Lin Hu; Weigang Xu; Haibin Dong; Xueli Qi; Chaojun Peng; Yu Zhang; Zhengling Li (BMC Plant Biology)
Abstract Background Historically, Henan Province has encountered multiple significant incidents of wheat cultivars resistance loss due to the emergence of new species of stripe rust fungus. To identify resistant germplasms exhibiting superior resistance to the emerging CRY34 strain, we employed a wheat 660 K array to genotype 256 Henan cultivars and conducted a genome-wide association study (GWAS) on adult plant resistance (APR) to wheat stripe rust in 2021–2022 and 2022–2023. Results A total of 48 SNP markers were found to be significantly correlated with APR. Fifteen were consistently detected using multi-locus GWAS methods in both BLUP values and in at least one field season. Among these 15 stable quantitative trait nucleotides (QTNs), 12 were previously reported and three were novel. The major novel QTN QYr.hnk-7DL was located at chr07DL_AX-111,720,006. Twelve associated cultivars possessing this QTN demonstrated high APR to stripe rust, with a 4.69% favorable genotype frequency. The chr07DL_AX-111,720,006 SNP was developed into the KASP marker KASP-YrZM1354 for easier detection. The validity of QYr.hnk-7DL was confirmed using KASP-YrZM1354 in two natural populations and three F2 populations. Through gene expression analysis within the candidate interval region, TraesCS7D01G544100 (designated YrZM1354) was identified as the candidate gene for QYr.hnk-7DL. Conclusions we identified and verified the major QTN QYr.hnk-7DL associated with APR to stripe rust, elucidated the candidate gene YrZM1354 at this locus, and developed the high-precision marker KASP-YrZM1354. This marker has been successfully used in resistant germplasm screening and wheat breeding.